Clinicians' practices regarding blind versus open weighing among patients with eating disorders. Issue 7 (12th December 2014) - Forbush, Kelsie T.; Richardson, Jonathan H.; Bohrer, Brittany K.
ABSTRACT Background Empirically supported treatments for eating disorders, such as cognitive‐behavioral therapy and family‐based treatment, stress the importance of weighing patients during therapy and using this information as part of treatment. However, weighing practices vary widely across eating disorders professionals, including those that purport to provide empirically supported interventions. Objectives To characterize clinicians' practices regarding the decision to share (open weighing) or withhold (blind weighing) weight information with patients, a topic that has received limited prior attention. Method Clinicians (N = 114; 85% female) who regularly treat individuals with an eating disorder completed an online survey to identify factors that might impact their decision to practice blind or open weighing. Results Approximately half of the clinicians reported generally using open weighing procedures (n = 53; 46.49%). Endorsement of cognitive‐behavioral or family‐based therapeutic orientation was not significantly associated with open weighing. However, clinicians who endorsed therapeutic modalities that do not specifically encourage open weighing were significantly more likely to engage in blind weighing. Clinicians working with clients with anorexia nervosa were significantly more likely to practice blind weighing, compared to clients with other eating disorder diagnoses, and cognitive or emotional impairment from malnutrition emerged as the strongest predictor of clinicians' decisions to practice blind weighing, controlling for all other variables. Discussion Development of specific training modules may be useful for improving adherence to empirically supported protocols that recommend open weighing. More importantly, however, our results highlight the need for future treatment studies to identify whether blind or open weighing is beneficial for improving patient outcomes. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:905–911)